51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-818
|View full text |Cite
|
Sign up to set email alerts
|

Field Testing LIDAR-Based Feed-Forward Controls on the NREL Controls Advanced Research Turbine

Abstract: Researchers at the National Renewable Energy Laboratory (NREL) and the University ofStuttgart are designing, implementing, and testing advanced feedback and feed-forward controls for multimegawatt wind turbines that will help reduce the cost of wind energy. Past wind turbine controllers have depended on turbine feedback measurements to determine the controller pitch commands. In this setup, wind speed disturbances can only be corrected after their effects have been detected in the turbine's loads and dynamic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 14 publications
1
58
0
3
Order By: Relevance
“…There have been numerous ongoing studies into the means by which LIDAR can improve wind turbine control performance. LIDAR-assisted collective pitch control for load reduction is one option and has actually been demonstrated recently in field testing [1], [2]. Another potential beneficial use of LIDAR is to increase energy yield by LIDAR-assisted yaw control [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous ongoing studies into the means by which LIDAR can improve wind turbine control performance. LIDAR-assisted collective pitch control for load reduction is one option and has actually been demonstrated recently in field testing [1], [2]. Another potential beneficial use of LIDAR is to increase energy yield by LIDAR-assisted yaw control [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Da wie in dieser Arbeit zwar die mittlere Windgeschwindigkeit in der Adaption des Filters beachtet wurde, die Wellenzahl jedoch nicht nachgeführt wurde, erhöhte sich in den Abschnitten mit schlechterer Korrelation durch einen Messfehler die Standardabweichung der Generatordrehzahl um circa 30 %. Mit einem kommerziellen System mit drei festen Messpositionen auf der CART3 konnte nur eine maximale kohärente Wellenzahl von 0,03 rad/m erreicht werden [8]. Damit konnte die Standardabweichung der Generatordrehzahl um circa 10 % reduziert werden (Bild 13 unten).…”
Section: Adaptiver Filterentwurfunclassified
“…Damit konnte die Standardabweichung der Generatordrehzahl um circa 10 % reduziert werden (Bild 13 unten). Diese Ergebnisse bestätigen, dass mit der vorgeschlagenen Vorsteuerung auch unter realen Bedingungen eine Verbesserung in der Regelung erzielt werden kann, die unterschiedliche Erfassung der rotorBild 13 Spektren der Generatordrehzahl von Feldtests auf einer Forschungsanlage mit 2 Rotorblättern (oben, [7]) und mit 3 Rotorblättern (unten, [8]): Ohne Vorsteuerung (dunkelgrau); mit LIDAR basierter adaptiver Vorsteuerung (schwarz).…”
Section: Adaptiver Filterentwurfunclassified
“…LIDARs provide information about the future wind inflow seconds ahead, which can be used by novel control systems to promote better speed regulation and load alleviation. In recent years a number of studies related to LIDAR-enabled control has been reported [7] and feedforward control has already been tested on experimental turbines [13,14]. The approach used in the field tests [13,14] was to augment an existing feedback controller with a feedforward term.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years a number of studies related to LIDAR-enabled control has been reported [7] and feedforward control has already been tested on experimental turbines [13,14]. The approach used in the field tests [13,14] was to augment an existing feedback controller with a feedforward term. This technique has 2 also been investigated in [2] with various design methods, such as model-inverse, optimized FIR filter and shaped compensators, preview control, non-causal series expansion, zerophase-error tracking and adaptive methods.…”
Section: Introductionmentioning
confidence: 99%